2018
DOI: 10.1055/a-0723-3441
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil- and Platelet- to Lymphocyte Ratio in Patients with Euthyroid Hashimoto’s Thyroiditis

Abstract: Background Hashimoto's thyroiditis (HT) is the most prevalent autoimmune thyroid disorder. Both neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are reported to be increased in various inflammation-related diseases, but their clinical significance in HT remains unclear. Objectives The aim of this study was to investigate the relationship between thyroid autommunity and NLR and PLR as markers of systemic inflammation in HT. Methods In this study, we evaluated 145 women with HT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
2
27
0
2
Order By: Relevance
“…Whereas, in a study by Cıray et al there was no difference among NLR between the patients with or without diabetic retinopathy (23). Also there are studies in which Hashimoto thyroiditis, which is one of the autoimmune thyroid diseases, is found to be signifi cantly higher than in the NLR and PLR control group (24) and before treatment than after levothroxine replacement (22). Despite the development of a similar autoimmune process with Graves' disease in Hashimoto thyroiditis, the thyroid hormone levels and the used medication are different.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Whereas, in a study by Cıray et al there was no difference among NLR between the patients with or without diabetic retinopathy (23). Also there are studies in which Hashimoto thyroiditis, which is one of the autoimmune thyroid diseases, is found to be signifi cantly higher than in the NLR and PLR control group (24) and before treatment than after levothroxine replacement (22). Despite the development of a similar autoimmune process with Graves' disease in Hashimoto thyroiditis, the thyroid hormone levels and the used medication are different.…”
Section: Discussionmentioning
confidence: 91%
“…Ulu et al reported a signifi cant association between NLR and diabetic retinopathy (21). Bilge et al found that NLR and PLR were higher in euthyroid Hashimoto patients than healthy controls (22). Whereas, in a study by Cıray et al there was no difference among NLR between the patients with or without diabetic retinopathy (23).…”
Section: Discussionmentioning
confidence: 96%
“…The cross-talk between blood platelets and lymphocyte have a potent effect on thyroid gland diseases [28]. So several attempts have been made to explore the connections between PLR and thyroid tumors and thyroiditis [29,30]. However, until now, no reported research has focused on the association between PLR and TN.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating WBCs and their classification counts will change, typically leading to lymphopenia and neutrophilia, in the presence of systemic inflammation (42,43). NLR is closely associated with most common inflammatory biomarkers, such as C-reactive protein and erythrocyte sedimentation rate (44)(45)(46)(47)(48)(49). A growing body of evidence suggests that NLR may act as excellent indicator of inflammation status in various diseases, such as Crohn's disease (49), cancer (50,51), infection (52,53), and rheumatic diseases (54)(55)(56).…”
Section: ' Discussionmentioning
confidence: 99%